The Effects of Cooperative Learning for Children with Disabilities in inclusion Classroom - Dr. Abdullah Abubakr (Kurdish Studies, 2024)
The purpose of this study was to give teachers' perspectives on the effects of cooperative learning inclusive classrooms. Eleven educators who employed cooperative learning strategies were interviewed for the study. The investigation explored how students with disabilities gained from cooperative learning, their participation in class activities, and the method's influence on their educational and behavioral growth. Results showed that teachers generally held positive views about cooperative learning for students with disabilities, although its efficacy varied among individual students. The study also found that students' academic achievements improved, particularly in writing skills. Additionally, students with disabilities in inclusive settings experienced enhanced social interactions and increased self-esteem through cooperative learning approaches. The current study recommends the need to consider students' perspectives on cooperative learning and the extent to which they benefit from it.